2003
DOI: 10.1074/jbc.m209655200
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Filamin to the C-terminal Tail of the Calcitonin Receptor Controls Recycling

Abstract: Many G protein-coupled receptors undergo endocytosis, but the mechanisms involved in endocytic sorting and recycling remain to be fully elucidated. We found that the G protein-coupled calcitonin receptor (CTR) undergoes tonic internalization and accumulates within the cell. Using a fluorescence loss in photobleaching assay, we classified these vesicles functionally as recycling vesicles. In a two-hybrid screening, we found that the actin-binding protein filamin interacted with the C-terminal tail of the CTR. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
79
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 31 publications
9
79
0
Order By: Relevance
“…Filamin A is known to bind to various membrane and signaling molecules, see reviews (Stossel et al, 2001;van der Flier and Sonnenberg, 2001)}. More recently different laboratories, including our own, demonstrated that filamin A associates with various GPCRs, such as the D2 and D3 dopamine receptors (Li et al, 2000;Lin et al, 2001), the calcium-sensing receptor (CaR) (Awata et al, 2001;Hjalm et al, 2001), the metabotropic glutamate receptor type 7 (Enz, 2002), alpha1-adrenergic receptors (Zhang et al, 2004), calcitonin receptor (Seck et al, 2003) and the mu opioid receptor (MOP) (Onoprishvili et al, 2003). In some cases, such as the calcium sensing receptor and the MOP, the binding of filamin A is to the carboxyl tail, while for other receptors, such as the D2 and D3 dopamine receptors, the binding is to the third cytoplasmic loop.…”
Section: Introductionmentioning
confidence: 99%
“…Filamin A is known to bind to various membrane and signaling molecules, see reviews (Stossel et al, 2001;van der Flier and Sonnenberg, 2001)}. More recently different laboratories, including our own, demonstrated that filamin A associates with various GPCRs, such as the D2 and D3 dopamine receptors (Li et al, 2000;Lin et al, 2001), the calcium-sensing receptor (CaR) (Awata et al, 2001;Hjalm et al, 2001), the metabotropic glutamate receptor type 7 (Enz, 2002), alpha1-adrenergic receptors (Zhang et al, 2004), calcitonin receptor (Seck et al, 2003) and the mu opioid receptor (MOP) (Onoprishvili et al, 2003). In some cases, such as the calcium sensing receptor and the MOP, the binding of filamin A is to the carboxyl tail, while for other receptors, such as the D2 and D3 dopamine receptors, the binding is to the third cytoplasmic loop.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is unclear, although the presence of a correctly organized submembranous actin cytoskeleton may be essential for the insertion or removal of proteins into or out of the plasma membrane. In support of this, binding of filamin to the carboxyl tail of the calcitonin receptor has been shown to be important in the recycling of the receptors back to the membrane after internalization (40).…”
Section: Filamin Binds To Inward Rectifier K ϩ Channelsmentioning
confidence: 99%
“…We confirmed this finding by use of a double-tagged Kir2.1 construct that allows us to monitor surface expression as a fraction of total expression. A number of other filamin-interacting proteins including ␤-integrins (28), K v 4.2 voltage-gated potassium channels (8), D2 dopamine receptors (7), and calcitonin receptors (40) show markedly decreased levels of functional cell surface expression in the absence of filamin. The reason for this is unclear, although the presence of a correctly organized submembranous actin cytoskeleton may be essential for the insertion or removal of proteins into or out of the plasma membrane.…”
Section: Filamin Binds To Inward Rectifier K ϩ Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…FLNA is a substrate for multiple kinases (reviewed in Sarkisian et al 2008) depending on whether or not its actin bound (Kawamoto and Hidaka 1984), with its cross-linking activity itself regulated by phosphorylation (Cukier et al 2007). FLN is a substrate for the Ca 2+ -activated protease calpain (Gorlin et al 1990) and for the ASB2 ubiquitin ligase (Heuze et al 2008) which provide irreversible regulatory mechanisms for severing FLN cross-links in processes requiring membrane and cytoskeleton remodelling such as cell migration (Marzia et al 2006;Baldassarre et al 2009) and receptor cycling (Seck et al 2003). FLN's role in cell motility and spreading appears to be cell-type dependent.…”
Section: Filamin Cellular Functionsmentioning
confidence: 99%